Could 101-14 Mgt Rootstock Affect Post-Spring Frost Vine Developing? Preliminary Findings - Gastón Gutiérrez-Gamboa; Cristóbal Palacios-Peralta; Nicolás Verdugo-Vásquez; Marjorie Reyes-Díaz; Ariel Muñoz; Alejandra Ribera-Fonseca (Horticulturae, 2024)
(1) Background: Spring frost damage is a common phenomenon that occurs in Southern Chile that considerably affects vine productivity and grape quality. (2) Methods: A field trial was conducted in order to study vine phenology and berry physicochemical parameters in Chardonnay, Sauvignon Blanc and Pinot Noir ungrafted and grafted (onto 101-14 Mgt rootstock) grapevines after a spring frost. This event killed the totality of primary bud shoots when the vines reached the phenological stage of unfolded leaves. (3) Results: From budburst, to flowering of secondary bud shoots, ungrafted Sauvignon Blanc grapevines presented an advanced phenology, whereas 101-14 Mgt rootstock tended to advance the maturity of Pinot Noir grapevines from flowering to ripening of berries. At harvest, berries from secondary buds of vines grafted onto 101-14 Mgt rootstock showed higher soluble solids than the ones from ungrafted Chardonnay and Sauvignon Blanc vines. High total phenolic content was found in berries from secondary buds of the grafted vines, compared to the ones from the ungrafted vines. Berry soluble solids variability tended to statistically decrease toward harvest in the studied plant materials, and the maximum coefficient of variation for soluble solids, berry weight, berry firmness and berry size reached 9.5%, 25.9%, 18.6% and 8.9%, respectively. (4) Conclusions: These preliminary results may be interesting for the Southern Chilean viticulturists since it seems that 101-14 Mgt rootstock could affect phenology and grape berry maturity of grapevines established in the Cautín Valley after spring frost damage.